(untitled) (African Journal of Law and Politics, 2023)
The current legal regime on OHADA law for companies in difficulties is based on a clearly distinct legislation, even if, as we will see, bridges are nonetheless established from one to another: the 2014 reform on the one hand, on commercial companies and EIGs with regard to companies likely to be restructured; and on the other hand, the 2015 reform relating to collective procedures for the clearing of debts, with regard to companies experiencing difficulties and likely to be recovered and revived. In view of the violent economic upheavals that the world has recently experienced and their repercussions on companies in the OHADA space, it is advisable to draw up, in this analysis, an overall picture of the measures taken for the effective transmission of the companies in difficulty.